2010
DOI: 10.1677/joe-09-0474
|View full text |Cite
|
Sign up to set email alerts
|

Response of adult mouse uterus to early disruption of estrogen receptor-α signaling is influenced by Krüppel-like factor 9

Abstract: Inappropriate early exposure of the hormone-responsive uterus to estrogenic compounds is associated with increased risk for adult reproductive diseases including endometrial cancers. While the dysregulation of estrogen receptor-a (ESR1) signaling is well acknowledged to mediate early events in tumor initiation, mechanisms contributing to sustained ESR1 activity later in life and leading to induction of oncogenic pathways remain poorly understood. We had shown previously that the transcription factor Krüppel-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
3
13
1
Order By: Relevance
“…Specifically, both Klf9 [22] and Klf13 (present study) null females exhibit normal steroid hormone production, as evidenced by their ability to normally cycle and achieve pregnancy. Although our results are not supported by the recent report that KLF9 and KLF13 are transcriptional activators of the steroidogenic genes LDLR, StAR, and CYP11A in ovarian granulosa cells [44], suggesting that loss of their respective expression should lead to reduced steroidogenesis, it is possible that the KLF9-regulated gene KLF4 [23] may take over the roles of KLF9 and KLF13 in a compensatory manner, as demonstrated for members of this family [25,45] (present study). Alternatively, KLF9 and KLF13 may compensate for each other's function in the context of the ovary.…”
Section: Heard Et Alcontrasting
confidence: 99%
See 3 more Smart Citations
“…Specifically, both Klf9 [22] and Klf13 (present study) null females exhibit normal steroid hormone production, as evidenced by their ability to normally cycle and achieve pregnancy. Although our results are not supported by the recent report that KLF9 and KLF13 are transcriptional activators of the steroidogenic genes LDLR, StAR, and CYP11A in ovarian granulosa cells [44], suggesting that loss of their respective expression should lead to reduced steroidogenesis, it is possible that the KLF9-regulated gene KLF4 [23] may take over the roles of KLF9 and KLF13 in a compensatory manner, as demonstrated for members of this family [25,45] (present study). Alternatively, KLF9 and KLF13 may compensate for each other's function in the context of the ovary.…”
Section: Heard Et Alcontrasting
confidence: 99%
“…The extent to which KLF9 plays a role in uterine function was previously demonstrated from our studies of female Klf9 null mice. We showed that Klf9 null mutation resulted in smaller litters due to reduced numbers of implanted embryos, a shift in the normal window of embryo implantation, partial uterine P 4 resistance, and enhanced uterine estrogen sensitivity [20,22,23]. Klf9 null mutation also dramatically influenced LE proliferative, apoptotic, and PGR expression status [22,24], consistent with LE as a target of stromal KLF9 through paracrine signaling.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Our laboratory has identified the transcription factor Krüppel-like factor (KLF) 9, an Sp-family member [9], as a transcriptional coregulator of ESR1 and PGR-B signaling in uterine cells [10][11][12][13][14][15]. KLF9 is expressed in uterine endometrial stroma and glandular, but not luminal, epithelium in mice [16], a finding recently confirmed for human endometrial cells [17].…”
Section: Introductionmentioning
confidence: 86%